Criação de um selo para autenticação de alimentos veganos utilizando métodos moleculares - RIBEIRO, Naiana Corrêa (2022)
With the increase in the number of vegans in recent years, along with the healthiest diets searching, the demand for plant-based foods has grown, giving rise to a promising commercial niche. However, to maintain the reliability of these products and ethical values required for that lifestyle, it’s necessary to authenticate them to ensure the absence of animal residues. In this research, the real-time polymerase chain reaction technique was used, targeting conserved regions of mitochondrial DNA in animals, in order to create a biomolecular certification for in natura and lightly processed foods. Using commercial kits with sensitivity threshold of 0.01% for animal DNA, greater specificity and speed in food authentication work was achieved, compared to other methods employed by the certifying bodies, currently used. The submitted products showed positive results for the seal and inhibitors-free from the observation of the reaction controls, which demonstrated the success of the method. Furthermore, the absence of animal elements in the samples was confirmed, and all of them are suitable to receive the vegan seal by genetic certification. Thus, collaborating in the ethical and economic valuation of those products and brands, ensuring trust to consumers and ease in the searches.